2022
DOI: 10.1111/dth.15408
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion after anti‐SARS‐CoV ‐2 mRNA vaccinations among moderate‐to‐severe psoriatic patients receiving systemic biologicals—Prospective observational cohort study

Abstract: It is unclear whether biological antipsoriatic therapies affect seroconversion after messenger ribonucleic acid (mRNA)‐based antisevere acute respiratory syndrome coronavirus 2 (anti‐SARS‐CoV‐2) vaccinations. To assess antibody formation and the incidence of side effects after anti‐SARS‐CoV‐2 mRNA vaccinations in psoriatic patients receiving different biologicals compared to healthy controls. 102 moderate‐to‐severe psoriatic patients (56.2 [±13.5] years) and 55 age‐matched healthy (56.4 ± 13.6 years) volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…The authors reported that all patients showed seroconversion after completed vaccination consisting of two doses, which fits in well with our findings (44,49). Other studies also presented similar findings (50)(51)(52)(53)(54)(55)(56). The main results of other studies that also investigated the serological response to COVID-19 vaccination in psoriasis patients are summarized in Table 4 Two of three patients without seroconversion received MTX.…”
Section: Discussionsupporting
confidence: 89%
“…The authors reported that all patients showed seroconversion after completed vaccination consisting of two doses, which fits in well with our findings (44,49). Other studies also presented similar findings (50)(51)(52)(53)(54)(55)(56). The main results of other studies that also investigated the serological response to COVID-19 vaccination in psoriasis patients are summarized in Table 4 Two of three patients without seroconversion received MTX.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, immunosuppressed patients had a lower incidence of AEs. Previous studies on IMDD patients' humoral immune responses in psoriasis, AIBD, and CSU patients showed no statistically significant differences from HCs (27,(32)(33)(34)(35)(36)(37). By stratifying participants of the IMDD group into individual diseases, Chanprapaph et al demonstrated that AIBD patients exhibit poor immune responses, whereas psoriasis patients develop comparable post-vaccination immune responses to a healthy population (32).…”
Section: Discussionmentioning
confidence: 99%
“…1 In order to evaluate the efficacy of vaccination on psoriatic patients receiving drugs potentially affecting immune system response, some studies have been performed. [2][3][4][5][6][7][8] However, such analyses only compared psoriatic patients with healthy controls. The aim of our study was to assess the rate of anti-SARS-CoV-2 neutralizing antibodies in psoriatic patients under topical and biological therapies after the completion of the first vaccination cycle with BNT162b2 vaccine and to verify whether there could be a difference between the different type of treatments.…”
Section: Seroconversion and Neutralizing Antibodies Production After ...mentioning
confidence: 99%